THE PRODUCTIVITY OF INDONESIAN E-COMMERCE: EVIDENCE FROM A DIGITAL MERCHANT SURVEY - Ilham Unggara; Endiarjati Dewandaru Sadono; Nur Hayatiningsih; Winny Isnasari Vellayati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The Indonesian government is aware of the enormous potential of e-commerce and provides various measures to support local products. However, many imported products are still present in Indonesian e-commerce. Through this study, we want to provide an analysis of the productivity of domestic products compared to imported products in shopee.com. Besides, this study also seeks to identify factors that affect sales. We find that the productivity of imported products is higher than domestic products. In order to increase the productivity of domestic products, the Government of Indonesia should continue to improve the logistics sector in order to lower transaction costs for domestic products and also provide support for small- and medium-sized enterprises (SMEs). We also found factors that affect average sales per month are price, seller's type and the length of time the seller joins shopee.com. Therefore, sellers in shopee.com should consider those factors to increase their sales.